(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The integration of electronic resources in teaching written translation has ushered in a new era of possibilities and efficiencies in language education. This article explores the multifaceted impact and the notable benefits of leveraging electronic resources in the pedagogical realm of written translation. Embracing the expansive array of digital tools and platforms, from translation memory software to online corpora and machine translation interfaces, has redefined the landscape of translation education. Through a comprehensive review of literature and practical case studies, this article sheds light on the transformative effects of electronic resources on enhancing translation competence, streamlining the translation process, and fostering a dynamic learning environment.